Cosmic evolution of stellar quenching by AGN feedback: clues from the Horizon-AGN simulation - Beckmann, R; Devriendt, J; Slyz, A; Peirani, S; Richardson, M; Dubois, Y; Pichon, C; Chisari, N; Kaviraj, S; Laigle, C; Volonteri, M (Oxford University Press, 2017)
The observed massive end of the local galaxy stellar mass function is steeper than its predicted dark matter (DM) halo counterpart in the standard $Λ $CDM paradigm. We investigate how active galactic nuclei (AGN) feedback can account for such a reduction in the stellar content of massive galaxies, through an influence on the gas content of their interstellar (ISM) and circum-galactic medium (CGM). We isolate the impact of AGNs by comparing two simulations from the HORIZON suite, which are identical except that one includes super massive black holes (SMBH) and related feedback. This allows us to cross-identify individual galaxies between these simulations and quantify the effect of AGN feedback on their properties, such as stellar mass and gas outflows. We find that the most massive galaxies ($ \rm M_{*} ≥ 3 × 10^{11} M_\odot $) are quenched to the extent that their stellar masses decrease by about 80% at $z=0$. More generally, SMBHs affect their host halo through a combination of outflows that reduce their baryonic mass, particularly for galaxies in the mass range $ \rm 10^9 M_\odot ≤ M_{*} ≤ 10^{11} M_\odot $, and a disruption of central gas inflows, which limits in-situ star formation, particularly massive galaxies with $ \rm M_{*} ≈10^{11} M_\odot $. As a result of these processes, net gas inflows onto massive galaxies drop by up to 70%. Finally, we measure a redshift evolution in the stellar mass ratio of twin galaxies with and without AGN feedback, with galaxies of a given stellar mass showing stronger signs of quenching earlier on. This evolution is driven by a progressive flattening of the $\rm M_{SMBH}-M_* $ relation for galaxies with $\rm M_{*} ≤ 10^{10} M_\odot $ as redshift decreases, which translates into smaller SBMHs being harboured by galaxies of any fixed stellar mass, and indicates stronger AGN feedback at higher redshift.